The influence of accelerated aging on the physical and chemical properties of a composite material: a systematic overview - S. M. Abdulkerimova; A. A. Kulikova; M. Yu. Dashtieva (Эндодонтия Today, 2021)
Relevance. Today, dental composite materials are very popular among dentists. The composite material is a filler in the form of particles of various sizes immersed in a polymer matrix. Polymer composites are used for direct filling of all groups of teeth and at different depths of the lesion. Composite materials have optimum mechanical, aesthetic and functional properties. They are simple and easy to use, provide long-term restoration service, and also have a wide price range. All these qualities allowed composite materials to firmly gain a foothold in the practice of dentists around the world. In this regard, clinicians and researchers are constantly trying to significantly improve their physical, mechanical, adaptive and aesthetic properties.Aim. Conduct a systematic assessment of the available scientific data on the effect of accelerated aging of the composite on its physicochemical properties.Materials and methods. In the course of a systematic review of the literature, a study was made of publications in electronic databases such as Google Scholar, PubMed, Research gate, Elibrary. The search results are formatted using the Prisma diagram.Results. Dental composites inevitably age over time and under the influence of environmental factors. To predict the long-term service life of composite restorations, scientists and clinicians are studying the aging behavior of the material. To simulate the clinical conditions of the oral cavity, various methods of artificial aging of dental composite materials have been developed.Conclusions. A study of scientific papers published over the past 10 years on the topic of artificial aging of dental composite materials has shown its unambiguous effect on the mechanical and morphological properties of polymers. The use of methods for simulating clinical conditions made it possible to reduce the study time and analyze the changes obtained.